Penentuan Tipe Fender Dermaga Untuk Kapal Multipurpose Berukuran Maksimum 30.000 DWT - Shabrina Rachma Putri (Fakultas Teknik Transportasi dan Logistik Trisakti, 2023)
Fender is one of the most important parts of a wharf planning, which has a function as a cushion that is useful for absorbing impact energy from ships. Therefore, in selecting the type fender really need to pay attention to several things, one of which is the capacity of the ship. Bungkutoko Kendari Special Terminal plans to build a wharf multipurpose with a vessel capacity of 30,000 DWT. The calculation of the ship capacity refers to two different types of ships nameny container and general cargo. The purpose of this study to determine the value berhing energy, choose a type super cone fender based on value berthing energy, knowing the value of the impact force to the reaction energy of the type super cone fender the chosen. The ship data used is secondary data obtained from related companies and agencies and then analyzed to calculate the value berthing energy, distance between fenders, and impact force. The results of the research show value berthing energy obtained is 592 kNm for container ships and 316.45 for ships general cargo. Therefore selected type fender SCN 1.150H F 1.2 and SCN 950H F 1.0 with ideal mounting distances fender of 4.6 meters.